Development of a Safe Raw Material Management System for Health-Focused Chinese Banquets - Kwanyupa Srisawang; Pornpan Usuwan; Saowanee Kongsri (Food Studies: An Interdisciplinary Journal, 2026)
This mixed-methods, participatory study co-designed and tested two linked interventions for the health-focused Chinese banquet sector: (1) a post-harvest management system to secure safe agricultural, livestock, and fishery inputs and (2) a multi-device website/database to manage raw-material orders. Participants included thirty producers (crops, livestock, and fisheries), nineteen banquet entrepreneurs, and relevant agencies. Data were gathered via semi-structured interviews, focus-group guides, and two evaluation instruments (system usability/efficiency; website effectiveness). Quantitative responses were analyzed using descriptive statistics (frequency, percentage, mean, standard deviation) and qualitative data via content analysis with peer validation. Producers prioritized a centralized, category-based management hub to coordinate safe products, smooth seasonal supply–demand mismatches, and expand underused online channels. Entrepreneurs required an accessible interface with clear specifications, pricing, provenance, and logistics options to reduce procurement time and input costs. Overall satisfaction was high (post-harvest system mean = 4.06; website/database mean = 4.04), indicating strong perceived efficiency, data quality, searchability, and support. The results demonstrate a feasible farm-to-banquet integration model that improves coordination and transparency, elevates product value, and strengthens local food system resilience. Theoretically, the work operationalizes a practical, context-specific digital intermediation approach for safe-food supply chains; in practice, it offers a transferable template for provinces seeking to align post-harvest governance, market access, and health-oriented culinary services.